(9E)‐9‐Benzylidene‐2‐methylsulfanyl‐5‐phenyl‐6, 7, 8, 9‐tetrahydropyrimido[4, 5‐b]quinolin‐4(3H)‐one: a hydrogen‐bonded R22(8) dimer. (12th November 2013) - Becerra, Diana; Insuasty, Braulio; Cobo, Justo; Glidewell, Christopher
<x xml:space="preserve">Abstract</x> In the molecule of the title compound, C25H21N3OS, which was prepared by mild oxidation of the corresponding 5, 6, 7, 8, 9, 10‐hexahydro analogue, the fused carbocyclic ring adopts an envelope conformation. Pairs of molecules are linked into cyclic centrosymmetric dimers by pairs of inversion‐related N—H...O hydrogen bonds.